2004
DOI: 10.1523/jneurosci.1381-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dickkopf-1, a Negative Modulator of the Wnt Pathway, Is Associated with Neuronal Degeneration in Alzheimer's Brain

Abstract: We used primary cultures of cortical neurons to examine the relationship between ␤-amyloid toxicity and hyperphosphorylation of the tau protein, the biochemical substrate for neurofibrillary tangles of Alzheimer's brain. Exposure of the cultures to ␤-amyloid peptide (␤AP) induced the expression of the secreted glycoprotein Dickkopf-1 (DKK1). DKK1 negatively modulates the canonical Wnt signaling pathway, thus activating the tau-phosphorylating enzyme glycogen synthase kinase-3␤. DKK1 was induced at late times a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
340
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(355 citation statements)
references
References 37 publications
13
340
0
2
Order By: Relevance
“…Dkk1 is induced in degenerating neurons from Alzheimer patients as well as in cultured neurons challenged with b-amyloid peptide. Dkk1 may promote apoptosis in Alzheimer neurons by enhancing Gsk3-mediated phosphorylation of the Tau protein in b-amyloid-treated neurons (Caricasole et al, 2004). Dkk1 is also induced in neurons subjected to ischemic insults, and antisense knockdown of Dkk1 shows some protection against neuronal apoptosis (Cappuccio et al, 2005).…”
Section: Other Roles Of Dkk1mentioning
confidence: 99%
“…Dkk1 is induced in degenerating neurons from Alzheimer patients as well as in cultured neurons challenged with b-amyloid peptide. Dkk1 may promote apoptosis in Alzheimer neurons by enhancing Gsk3-mediated phosphorylation of the Tau protein in b-amyloid-treated neurons (Caricasole et al, 2004). Dkk1 is also induced in neurons subjected to ischemic insults, and antisense knockdown of Dkk1 shows some protection against neuronal apoptosis (Cappuccio et al, 2005).…”
Section: Other Roles Of Dkk1mentioning
confidence: 99%
“…On the other hand, activation of both GSK3a and GSK3b through their autophosphorylation has been implicated in AD pathogenesis (Caricasole et al, 2004). Although there may be some crosslinking between GSK3a and GSK3b proteins, increased GSK3a activity is mainly involved in APP processing and Ab generation (Phiel et al, 2003), whereas activation of GSK3b is predominantly associated with tau phosphorylation and neurofibrillary tangle formation (Baum et al, 1996;Ma et al, 2006).…”
Section: Hupa Is Involved In Regulation Of the Wnt Signaling Pathwaymentioning
confidence: 99%
“…b-Catenin levels are significantly reduced in AD individuals bearing presenilin mutations (Zhang et al, 1998) and active GSK3b accumulates in vivo in AD brains (Pei et al, 1999), where it has a key role in the hyperphosphorylation of the microtubule-associated protein tau (Hanger et al, 1992;Lovestone et al, 1994;Lucas et al, 2001;Sato et al, 2002;Li et al, 2006). Moreover, Wnt signaling may also have an essential role in the processing of the amyloid precursor protein (Mudher et al, 2001;Sun et al, 2002;Phiel et al, 2003), as well as in the neurotoxicity of its derivative the amyloid b-peptide (Ab) (Takashima et al, 1998a;Alvarez et al, 2002;De Ferrari et al, 2003;Alvarez et al, 2004;Caricasole et al, 2004). Remarkably, it has been reported that Ab neurotoxicity induces the expression of Dickkopf 1 (Dkk1) (Caricasole et al, 2004), which may further antagonize Wnt presentation to its complex receptor.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%
“…Moreover, Wnt signaling may also have an essential role in the processing of the amyloid precursor protein (Mudher et al, 2001;Sun et al, 2002;Phiel et al, 2003), as well as in the neurotoxicity of its derivative the amyloid b-peptide (Ab) (Takashima et al, 1998a;Alvarez et al, 2002;De Ferrari et al, 2003;Alvarez et al, 2004;Caricasole et al, 2004). Remarkably, it has been reported that Ab neurotoxicity induces the expression of Dickkopf 1 (Dkk1) (Caricasole et al, 2004), which may further antagonize Wnt presentation to its complex receptor. All together the data indicate that the activity of Wnt signaling components is compromised in AD brains and thus underlies Ab generation/toxicity/deposition and tau hyperphosphorylation, major pathological hallmarks of this neurodegenerative condition (De Ferrari and Inestrosa, 2000;Mudher and Lovestone, 2002;Caricasole et al, 2003;Moon et al, 2004).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%